PEMANFAATAN MEDIA EVALUASI PEMBELAJARAN SOCRATIVE PADA MATA PELAJARAN BAHASA INDONESIA - Heni Suci Arti (Jurnal Komposisi, 2021)
ICT-based education is something that is used during the current pandemic. The Covid-19 pandemic has had an impact on the world of education, which not only affects one level, but also affects all levels of education. The use of ICT-based learning media can be used as one of the media that can be used by teachers in distance learning. Evaluation media that is suitable to be used is socrative. Socrative is a student response system that allows teachers to create interactive quizzes or games and involve students directly. This research uses descriptive-qualitative method because the data used are words and the final result is a description. This research was motivated because the world of education during the Covid-19 pandemic was like doing distance learning. This makes teachers and students obliged to carry out learning at home. It seems to have an impact on presenting the material given by the teacher to students. This study aims to introduce online-based learning media that can be used in distance learning as it is today. Socrative is a learning evaluation media that is used as a practice question that is used as a benchmark for students after being given the material by the teacher. This medium is included in easy media and has various forms of quiz. In addition, you can use it via the web without first downloading the application. This media is suitable for use in Indonesian language learning which requires all students to have the ability in good and correct language. This research discusses the steps for using and using socrative media.